Residential Demand for Electricity and Natural Gas in Pakistan (The Pakistan Development Review, 1983)
A model for residential demand for fuel in Pakistan was developed on the basis of stock of fuel-consuming appliances and their rate of utilization. Income and price elasticities of natural gas and electricity are estimated by the OLS and GLS methods. The income elasticity of natural gas and electricity and price elasticity of natural gas are found statistically significant and consistent with a priori knowledge of economic theory. Several policy implications are pointed out and suggestions are made for improvement in future estimations.